Towards Determination of Inductive Resistances of Single-Core Cables with Voltage of up to 1 kV Insulated by Cross-Linked Polyethylene - V. N. Radkevich; V. V. Stalovich; D. S. Alekhnovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2018)
To calculate short-circuit currents, voltage losses and reactive power in electrical networks, information on inductive resistances of cable lines is required. In the technical literature there are no exact parameters of single-core cables with voltage of up to 1 kV insulated by crosslinked polyethylene. This results in inaccuracies in the calculations of modes of electrical networks. The article considers the issues of determining the inductance and inductive resistance of power lines up with voltage of up to 1 kV made of single-core cables and insulated by crosslinked polyethylene. The analysis of formulas for determining the inductance given in different literature sources was fulfilled, that demonstrated a significant difference in the numerical values of the obtained calculation results. The formula that provides more reliable calculations of the inductance of the cable lines was identified. The influence of the permissible increase in the thickness of the insulation and the sheath of a single-core cable with voltage of up to 1 kV covered with cross-linked polyethylene on the inductive resistance was determined. The inductance and inductive resistance of single-core cables were calculated when the cables were arranged along the vertices of an equilateral and right-angle triangle, as well as in one plane. It was shown that the specific inductances and inductive resistances are 1.7–1.8 times greater in the plane with the distance between adjacent cables equal to the outer diameter of the cable than in the location is close to the triangle. When the cross sections of conductive cores are large and installations are multi-ampere, there is a surface effect and proximity effect, due to which the magnetic field intensity inside the core and its inductance decrease. Inductivities and inductive resistances of singlecore cables with voltage up to 1 kV were determined taking into account the influence of the surface effect and the proximity effect. The calculations that we performed have shown that the nonconsideration of the above-mentioned effects leads to significant errors in the determination of inductive resistances. The influence of one-core cables of armor made of steel tapes on inductive resistances is considered. An illustrative example shows that the inductive resistance of an armored cable with a cross-section area of the current-conducting core equal to 800 mm2 is about twice as large as the unarmored one. The use of single-core cables in three-phase electrical networks, armored with steel straps, ought to be prohibited by regulatory documents, since such cables dramatically worsen the efficiency of power supply systems.